Negotiating Marriage Preparation: Generation Z Muslims’ Views on Premarital Guidance in Madura - Asyhari, Asyhari; Taufiq, Muhammad; Azhari, Jalaludin Faruk; Imamuddin, Imamuddin (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2025)
Abstract: This study explores the mixed attitudes of Muslim Generation Z towards premarital counseling in Branta Tinggi village, Madura, Indonesia. Born between 1995 and 2010, Gen Z shows a shift from traditional-religious marriage models to more rational-religious approaches, influenced by digital exposure to marriage challenges and economic uncertainties. Field research in Branta Tinggi reveals that, although Gen Z respects premarital counseling as both a religious and social necessity, they also view it with skepticism due to concerns about its administrative nature and effectiveness. The study finds a dual perspective: premarital counseling is not a religious requirement for a valid marriage according to fiqh, but it is mandatory for state recognition under Indonesian law. Participants have specific expectations for the content and delivery of counseling, favoring interactive, ICT-based approaches that cover sensitive topics thoroughly rather than idealized presentations. Overall, this research sheds light on how digital-native generations balance traditional values with modern rationality in marriage preparation, offering insights for religious institutions and policymakers aiming to improve the effectiveness of premarital counseling.